Habituation of Anti-Corruption Values on Children in Orphanages - Marasabessy, Abd. chaidir; Siagian, Amrizal; Istianingsih, Istianingsih; Novi, Febry (Fakultas Keguruan dan Ilmu Pendidikan Universitas Pamulang, 2023)
Dishonorable behavior by taking other people's belongings is often carried out by teenagers in social institutions. These actions occur because they experience financial, social and emotional problems. Precautions must be taken to ensure the next generation does not behave corruptly. Locus of service of Ciputat Women's Charity Orphanage, South Tangerang. The partner's goal is to create an anti-corruption atmosphere and culture through anti-corruption-based activities; And students as service members have sensitivity and are able to photograph real conditions so that their creativity develops in cultivating anti-corruption behavior. Participatory action research is the method used. This service activity has succeeded in fostering anti-corruption cultural behavior in partners. The results of the questionnaire showed that of the 38 participants who participated in the anti-corruption values habituation activity, 34 people gave statements of